(untitled) (Asian Journal of Pharmaceutics (AJP), 2024)
Objective: This study aimed to find a way to make buccal tablets of Paroxetine Hydrochloride (PRX) that stick to mucous membranes effectively and have a controlled release. Materials and Methods: Response surface approach, notably a three-level strategy, and Design Expert® software were used to develop and optimize Paroxetine Hydrochloride buccal tablets for oral medication delivery. PRX’s unidirectional mucoadhesive buccal tablets were prepared by direct compression using Carbopol 934P and HPMC K15M as mucoadhesive controlled release agents. The developed formulations were assessed for a variety of characteristics before and after compression, as well as for surface pH, swelling, ex vivo mucoadhesive strength, and in vitro and ex vivo drug release. Results: The Fourier-transformed infrared spectrum and differential scanning calorimetry peak of Paroxetine Hydrochloride indicated that there was no interaction between the drug and the used excipients. Swelling index research found that polymer concentration is directly correlated with swelling. Formulation F4 Paroxetine Hydrochloride exhibited the highest mucoadhesive strength (0.93 ± 0.06N) with the highest ratio of carbopol 934P and HPMC K15M (2:5), while formulation F11 had the weakest force (0.68 ± 0.04N) due to higher and lower polymer quantities. In in vitro release trials, tablet formulation F9 demonstrated superior release characteristics (95.57 ± 0.42%, 8 h) compared to other formulations due to carbopol 934P and HPMC K15M swelling, drug release was slow (0–63.34%) for the first 4 h. Drug release increased from 4 to 8 h, reaching 95.57 ± 0.42% by the end. Ex vivo permeation research using drug release experiments identified formulation F9 as the best, with a 70.88 ± 2.65% drug release compared to 42.65 ± 2.52%. Conclusion: The ideal controlled release system would release the medication at the right time and keep it at the therapeutic level for as long as possible. According to dissolving profiles and swelling data, mucoadhesive buccal tablets released Paroxetine Hydrochloride mostly due to the quickly hydrating polymer. This study aimed to bypass first-pass metabolism and increase Paroxetine Hydrochloride bioavailability.